Preparation and application of a class of nonionic amphiphilic compounds with mixed polymer structures
By designing non-ionic amphiphilic compounds with mixed polymerization structures of propylene oxide and ethylene oxide, and preparing non-ionic-anionic composite surfactants through the sulfurization process, the existing surfactants have been solved, and the effective reduction of interfacial tension and excellent oil repellency performance are achieved.
Patent Information
- Application Number
- CN202111395704.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-23
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-11-23
AI Technical Summary
It is difficult for existing surfactants to achieve excellent temperature and salt resistance in high-temperature and high-salt environments, and it is difficult to obtain hydrophilic and lipophilic balance, resulting in difficulty in reducing interfacial tension.
A nonionic amphetamine compound with a mixed structure of propylene oxide (PO) and ethylene oxide (EO) was designed. By mixing cubet alcohol or bisalkyl glycerol ether with PO and EO, a structure with a double long chain alkyl group is formed, and a nonionic-anionic composite surfactant is further prepared by a sulfation process.
It achieves excellent salt resistance and high temperature stability of surfactants, can form a single molecular layer at the oil/water interface, reduces the interface tension to an ultra-low level, and is suitable for technical fields such as three oil production.
Smart Images

Figure CN114106316B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation and application of a class of nonionic amphiphilic compounds with a mixed polymer structure, belonging to the technical field of fine chemical industry, and also to the technical field of surfactants, colloids and tertiary oil recovery. Background Art
[0002] In recent years, my country's dependence on foreign crude oil has increased year by year, and has now exceeded 70%. Therefore, increasing domestic crude oil production is an urgent task. However, conventional oil recovery technologies, such as primary oil recovery (self-flowing) and secondary oil recovery (water injection), can only recover 30-40% of the total reserves, that is, more than 60% of the crude oil still remains underground. Studies have shown that through tertiary oil recovery technology, residual oil accounting for about 20% of the total reserves can be further recovered, and tertiary oil recovery technology with the help of surfactants is suitable for most oil fields in my country.
[0003] Most of my country's oil fields are high-temperature, high-salinity reservoirs. Accordingly, the surfactants used for oil displacement (called oil displacement agents) must have excellent temperature and salt resistance. Conventional ionic surfactants are generally sensitive to electrolytes and are therefore not suitable for use as oil displacement agents. Non-ionic surfactants are sensitive to temperature and often have a cloud point phenomenon, so they are also not suitable for use as oil displacement agents alone.
[0004] Studies have shown that the introduction of nonionic hydrophilic groups, such as polyoxyethylene (EO) groups, into the molecular structure of ionic surfactants can significantly improve the salt tolerance of surfactants. For nonionic surfactants, if ionization is performed, that is, an ionic hydrophilic group is connected, the cloud point phenomenon will also be weakened or disappear. Obviously, this type of surfactant with nonionic-anionic composite hydrophilic groups has excellent temperature and salt resistance, so it has received widespread attention.
[0005] However, common nonionic-anionic composite surfactants, such as fatty alcohol polyoxyethylene ether sulfate (AES), are still not suitable for use as oil displacement agents, because surfactant oil displacement requires surfactant molecules to be adsorbed on the crude oil / water interface to form a monolayer, reducing the oil / water interfacial tension to an ultra-low level (<0.01mN / m). In order to achieve this goal, the surfactant molecules must achieve a hydrophilic-lipophilic balance in structure, that is, the hydrophilicity and lipophilicity of the surfactant are basically equivalent, and the hydrophilic and lipophilic parts should be as large as possible to obtain a stronger hydrophilic and lipophilic interaction.
[0006] Generally, the hydrophilicity of conventional ionic surfactants is much greater than their lipophilicity. If polyoxyethylene groups are introduced into the molecules, the hydrophilicity will further increase, further deviating from the hydrophilic-lipophilic balance. Therefore, using a single anionic surfactant such as linear alkylbenzene sulfonate (LAS), sodium dodecyl sulfate (SDS), sodium α-olefin sulfonate (AOS), and sodium fatty alcohol polyoxyethylene ether sulfate (AES) generally cannot achieve ultra-low interfacial tension.
[0007] Obviously, to achieve a hydrophilic-lipophilic balance, the chain length of the lipophilic group must be increased, but this is limited by the source of raw materials. The raw materials used to prepare surfactants are mainly natural oils and petrochemicals. The alkyl chain length of natural oils is mainly C 12 To C 18 , the alkyl chain length is higher than C 18 The production of natural oils is extremely low and the price is high, which cannot meet the demand. Similar to petrochemical products, the raw materials with large production and mature production technology, such as alkylbenzenes, fatty alcohols, alkylphenols, etc., generally have alkyl chain lengths of no more than C 18 .
[0008] Even if the alkyl chain length can be increased to C 18 The above will lead to another problem, namely the solubility problem. The solubility of single-chain alkyl surfactants in aqueous solution decreases with the increase of alkyl chain length. 18 When the surface is low, it may not dissolve in water, and in highly mineralized water, the solubility is even lower or even insoluble. Therefore, in order to obtain a hydrophilic-lipophilic balanced surfactant and ultra-low interfacial tension, a new design of the surfactant structure is required. Summary of the invention
[0009] The present invention relates to a novel nonionic amphiphilic compound structure design, preparation process and application. The nonionic amphiphilic compound with the novel structure can be used directly as a nonionic surfactant, or as an intermediate, and further processed into a nonionic-anionic composite surfactant for use in the technical fields of tertiary oil recovery and the like.
[0010] The present invention provides a compound having a mixed structure of propylene oxide (PO) and ethylene oxide (EO), which is prepared by mixing alcohols containing a double long-chain alkyl group with PO and EO, and has the following structure RA-R';
[0011] A is a structure formed by the polymerization of PO and EO U1 and U2 are different and can be independently selected from: *-O-CH2CH2-*, and is not the following block structure x is the number of moles of PO, selected from an integer between 5 and 40; y is the number of moles of EO, selected from an integer between 5 and 30;
[0012] R' is H, -SO3Na;
[0013] R is derived from gubetaine alcohol or dialkyl glyceryl ether, and is the following structure containing two long-chain alkyl groups:
[0014] or
[0015] Wherein, R1 and R2 are selected from C4~C 16 Alkyl; R3 is selected from C6~C 18 Alkyl, R4 is selected from C6~C 18 alkyl.
[0016] In one embodiment of the present invention, A is a structure formed by the polymerization of PO and EO, wherein the molar ratio of PO to EO is x:y, ie (5-40):(5-30).
[0017] In one embodiment of the present invention, x is preferably an integer between 15 and 30; y is preferably an integer between 10 and 20.
[0018] In one embodiment of the present invention, R1 and R2 are both selected from C6 to C 16 alkyl.
[0019] The present invention also provides a method for preparing a nonionic amphiphilic compound, which is equivalent to the above structure RA-R' when R' is H, comprising the following steps:
[0020] Propylene oxide and ethylene oxide are premixed, and then gubetainol or dialkyl glycerol ether and a catalyst are added to carry out a mixed polymerization reaction in one pot under an inert atmosphere. After the reaction is completed, a compound having a mixed structure of propylene oxide (PO) and ethylene oxide (EO) is obtained, which is recorded as R (PO + EO). x+y H; x is the mole number of PO, selected from an integer between 5 and 40; y is the mole number of EO, selected from an integer between 5 and 30.
[0021] In one embodiment of the present invention, the structure of gubeterol is
[0022] The structure of dialkyl glyceryl ether is
[0023] In one embodiment of the present invention, the molar ratio of gubertol or dialkyl glyceryl ether, propylene oxide, and ethylene oxide is 1:(5-40):(5-30), preferably 1:(15-30):(10-20), and more preferably 1:30:15.
[0024] In one embodiment of the present invention, the temperature of the co-polymerization reaction is preferably 140-160°C.
[0025] In one embodiment of the present invention, the catalyst is a double metal cyanide catalyst (DMC catalyst).
[0026] In one embodiment of the present invention, the amount of the catalyst used is 100 ppm relative to the amount of the gubertyl alcohol or the dialkyl glycerol.
[0027] In one embodiment of the present invention, the co-polymerization reaction does not require a solvent and does not require purification after the reaction.
[0028] The present invention also provides a method for preparing a nonionic-anionic composite surfactant, which is equivalent to the above structure RA-R' when R' is -SO3Na, comprising the following steps:
[0029] (1) Propylene oxide and ethylene oxide are premixed, and then gubetainol or dialkyl glycerol ether and a catalyst are added to carry out a mixed polymerization reaction in one pot under an inert atmosphere. After the reaction is completed, a compound intermediate R (PO+EO) having a mixed polymerization structure of propylene oxide (PO) and ethylene oxide (EO) is obtained. x+y H; x is the number of moles of PO, selected from an integer between 5 and 40; y is the number of moles of EO, selected from an integer between 5 and 30;
[0030] (2) Use sulfating agent to treat intermediate R(PO+EO) x+y H is sulfated to obtain a nonionic-anionic composite surfactant R (PO+EO) x+y -SO3Na.
[0031] In one embodiment of the present invention, the sulfating agent comprises gaseous SO3, chlorosulfonic acid or aminosulfonic acid.
[0032] In one embodiment of the present invention, the sulfation process comprises: using gaseous SO3 as a sulfating agent, reacting the intermediate R(PO+EO) through a falling film reactor. x+y H for sulfation.
[0033] In one embodiment of the present invention, in a falling film reactor, a SO3 / air mixture is used as a sulfating agent, and the SO3 concentration is ≤5% (v / v). Specifically, a 4%-5% (v / v) SO3 / air mixture can be selected.
[0034] In one embodiment of the present invention, the intermediate R(PO+EO) x+y The molar ratio of H to SO3 is 1:1.05.
[0035] In one embodiment of the present invention, the reaction temperature is 55-60° C., and after the reaction is completed, the solution is neutralized with an aqueous NaOH solution to a pH of 8-9.
[0036] In one embodiment of the present invention, the sulfation process further comprises: using chlorosulfonic acid as a sulfating agent, feeding according to a molar ratio of intermediate / chlorosulfonic acid of 1:1.05, reacting at a temperature of 30-40° C., and immediately neutralizing with an aqueous NaOH solution to a pH of 8-9 after the reaction is completed.
[0037] The present invention also provides the use of the compound having a mixed structure of propylene oxide (PO) and ethylene oxide (EO) in the field of oil production.
[0038] Beneficial effects:
[0039] The novel nonionic amphiphilic compound of the present invention adopts a dialkyl structure, which breaks through the conventional surfactant alkyl chain length of no more than C 18 Based on the current market bulk raw materials, the total alkyl chain length can reach C 36 Therefore, the oil displacement surfactant derived from it can have strong lipophilicity.
[0040] The novel nonionic amphiphilic compound of the present invention can be directly used as a nonionic surfactant, especially as an intermediate to derive a nonionic-anionic composite surfactant, which is particularly suitable for use as an oil displacement agent and has excellent salt tolerance.
[0041] The nonionic-anionic composite surfactant derived from the intermediate of the present invention has a spatial transition structure when it is adsorbed on the oil / water interface. It transitions from a strong lipophilic (alkyl chain layer) to a weak lipophilic-weakly hydrophilic (PO-EO mixed chain layer) and then to a strong hydrophilic (ionic head group) layer, forming a transitional oil / water interface with considerable thickness. This monolayer structure changes the phase state of the original oil / water interface, making the difference of the oil / water interface almost disappear, so it is easier to obtain ultra-low interfacial tension.
[0042] Compared with the block structure, the novel nonionic intermediate of the present invention has a mixed structure, and the nonionic-anionic composite surfactant derived therefrom has excellent water solubility and salt resistance. When the hydrophilicity and lipophilicity reach a balance, a transparent solution can still be obtained. As an oil-displacing agent, the phenomenon of insolubility or precipitation of the surfactant due to increased lipophilicity is prevented.
[0043] The novel nonionic intermediate with PO-EO mixed structure of the present invention is a transparent liquid at room temperature with low viscosity, and can be used to prepare sulfate surfactant by SO3 falling film sulfation process without adding solvent, and the conversion rate is as high as 95% or more. However, the corresponding compound with block structure is difficult to form film due to high viscosity, and SO3 falling film sulfation process cannot be used. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Nonionic intermediate C 16 Cufibrate Alcohol(PO+EO) 30+15 Mass spectrum of H.
[0045] Figure 2 C 16 Cufibrate Alcohol(PO+EO) 30+15 Mass spectrum of SO3Na(APES).
[0046] Figure 3 The concentration of C is 10wt.% at room temperature. 16 Cufibrate Alcohol (PO+EO) 30+15 Photo of SO3Na(APES) aqueous solution.
[0047] Figure 4 At 25°C 16 Cufibrate Alcohol (PO+EO) 30+15 The surface tension of SO3Na(APES) aqueous solution varies with solution concentration.
[0048] Figure 5 The transmittance (600nm) of APES (1.25wt.%) dissolved in NaCl aqueous solution at 45℃ changes with the Na + Concentration variation graph.
[0049] Figure 6 APES (1.25 wt.%) dissolved in Ca at 45 °C 2+ The transmittance of Cl2 solution (600nm) varies with the concentration of Ca in the solution. 2+ Concentration variation graph.
[0050] Figure 7 The interfacial tension of a single APES (1.25 wt.%) dissolved in Daqing simulated formation water (total mineralization 7,000 mg / L) against normal alkanes with different carbon number at 45°C.
[0051] Figure 8 The interfacial tension (45°C) of single APES (1.25wt.%) dissolved in Daqing simulated formation water (total salinity 7,000mg / L) against Daqing light crude oil.
[0052] Fig. 9 APES / diC 10 Interfacial tension (45℃) of GE-HSB (didecylglycerol hydroxypropyl sulfobetaine) binary mixture (mass ratio = 85 / 15) dissolved in Daqing simulated formation water (total mineralization 7,000 mg / L) on crude oil from three types of Daqing reservoirs.
[0053] Fig.10 The nonionic intermediate C of the present invention 16 Cufibrate Alcohol (PO+EO) 30+15 H (middle) and AEO3 (left) and block intermediate C 16 Cufibrate-PO 30 -EO 15 H (right) exterior photo. DETAILED DESCRIPTION
[0054] Example 1 Preparation of nonionic surfactant / intermediate
[0055] C 16 Jubate alcohol (Sasol Nanjing) was used as raw material, and propylene oxide (PO) and ethylene oxide (EO) were added in the presence of a catalyst using a non-stirring circulating spray reactor. 16 The molar ratio of 1:30:15 of gubertol (R1 and R2 are both hexyl): PO:EO is added. First, the measured PO and EO are pre-mixed in a raw material tank to obtain a mixture; the gubertol is injected into the reactor, and a double metal cyanide catalyst (DMC catalyst) is added at a concentration of 100ppm (relative to gubertol), mixed evenly, evacuated, filled with nitrogen, and heated to 130°C. Nitrogen is pressed into the pre-mixed mixture of PO and EO for mixed polymerization, and the reaction temperature is controlled at 150°C by a circulating cooler until the reaction is completed, and the product is cooled and discharged. The reaction time is about 2h.
[0056] Figure 1 C 16 Cufibrate Alcohol (PO+EO) 30+15 Mass spectrum of H.
[0057] The obtained novel nonionic intermediate with PO-EO mixed structure is a transparent liquid at room temperature with low viscosity. The viscosity is measured to be 685 mpa·s at 25°C (rotation speed 30 rpm) and 184 mpa·s at 60°C (rotation speed 30 rpm).
[0058] Example 2 Preparation of nonionic-anionic (sulfate) surfactant
[0059] The nonionic intermediate C obtained in Example 1 16 Cufibrate Alcohol(PO+EO) 30+15H is used as an intermediate and further processed into sulfate through a sulfation process. SO3 gas / air mixture is used as a sulfating agent, and sulfation is carried out in a glass tube membrane sulfonator. SO3 / air mixture (SO3 gas concentration 5%, v / v), non-ionic intermediate / SO3 (molar ratio) = 1:1.05, reaction temperature 60°C, and immediately after the reaction is completed, NaOH aqueous solution is used to neutralize to pH = 8.5, and C 16 Cufibrate Alcohol (PO+EO) 30+15 SO3Na, recorded as APES, has a conversion rate of 95%.
[0060] Chlorosulfonic acid or aminosulfonic acid can also be used as a sulfating agent to react the intermediate R(PO+EO) x+y H for sulfation.
[0061] Figure 2 From its mass spectrum, it can be seen that APES is a homologous mixture with a wide molecular weight distribution.
[0062] Example 3 Surface activity test
[0063] The sulfate surfactant (APES) obtained in Example 2 was dissolved in deionized water at room temperature. When the concentration was as high as 10 wt.%, the solution remained transparent. Figure 3 shown.
[0064] C 16 Cufibrate Alcohol (PO+EO) 30+15 SO3Na(APES) was dissolved in deionized water and diluted to different concentrations. The surface tension of the solution was measured by the hanging ring method at 25°C. The surface tension-concentration curve was as follows: Figure 4 As shown in Figure 2, it can be seen that the critical micelle concentration of the surfactant is extremely low, about 0.00025wt.%, γ cmc It is about 38mN / m.
[0065] Example 4 Salt tolerance test
[0066] The APES obtained above was dissolved in a NaCl aqueous solution at 45°C, and the APES concentration was 1.25 wt.%. The transmittance of the solution was measured at a wavelength of 600 nm using a spectrophotometer, and a graph was plotted against the NaCl concentration in the solution to obtain the following: Figure 5 The curve shown. It can be seen that when the NaCl concentration in the aqueous solution is lower than 20,000 mg / L (equivalent to 2 wt.% NaCl), the transmittance of the aqueous solution is >90%. That is, the tolerance of APES to the monovalent inorganic salt NaCl can reach 20,000 mg / L. As the NaCl concentration increases further, the transmittance of the aqueous solution drops sharply, because the high salinity causes the surfactant to be insoluble in water, resulting in precipitation. As the precipitate settles or phase separation occurs, the transmittance of the solution rises again.
[0067] Similarly, the APES obtained above was dissolved in a CaCl2 aqueous solution at 45°C, the APES concentration was 1.25 wt.%, and the light transmittance of the solution was measured at a wavelength of 600 nm using a spectrophotometer. The CaCl2 concentration in the solution was plotted as follows: Figure 6 The curve shown shows that APEC's tolerance to divalent salt CaCl2 is about 1000 mg / L.
[0068] Example 5 Using surfactant alone to reduce interfacial tension
[0069] The APES obtained in Example 2 was dissolved in the simulated formation water of Daqing, the concentration of APES was 1.25wt.%, the total mineralization of the simulated formation water was 7,000mg / L, and the interfacial tension of a series of normal alkanes was measured by the rotating drop method at 45°C. The dynamic interfacial tension reached equilibrium within 20 to 30 minutes. The relationship between the equilibrium interfacial tension and the carbon number (ACN) of the normal alkane is as follows: Figure 7 As shown in the figure, it can be seen that the interfacial tension of APES to a series of normal alkanes is related to the carbon number of the alkanes, which is consistent with the law of general surfactants. 10~11 The interfacial tension of alkanes (decane to undecane) is the lowest, reaching 0.011 to 0.012 mN / m, while the equivalent carbon number of Daqing crude oil is C 10 Therefore, it can be judged that the hydrophilic-lipophilic balance of the sulfate APEC derived from the non-ionic intermediate obtained by the present invention matches well with the Daqing crude oil / formation water, and is very suitable for reducing the interfacial tension of the Daqing crude oil / formation water.
[0070] The sulfate APES in Example 2 was dissolved in the simulated formation water of Daqing, the APES concentration was 1.25wt.%, the total mineralization of the simulated formation water was 7000mg / L, and the interfacial tension of the Daqing light crude oil was measured by the rotating drop method at 45°C. The dynamic interfacial tension reached equilibrium within 60-90min. The equilibrium interfacial tension changed with the concentration as shown in Figure 8 It can be seen that APES alone can achieve ultra-low interfacial tension in a wide concentration range (0.25-2.5 wt.%).
[0071] It is usually difficult to obtain ultra-low interfacial tension with existing conventional surfactants alone, and they often need to be compounded, and the concentration range for obtaining ultra-low interfacial tension is relatively narrow. This shows the superiority of the non-ionic intermediate of the present invention: (1) The structural design of embedding PO and EO groups is adopted, which is conducive to adjusting the hydrophilic-lipophilic balance of the final product; (2) In terms of arrangement, a mixed polymerization method is adopted, so that the final sulfate derivative forms a gradient change from strong lipophilicity to weak lipophilicity-weak hydrophilicity and then to strong hydrophilicity; (3) The use of dialkyl chain-containing gubertol as the lipophilic group significantly increases the density of alkyl chains in the monolayer formed at the oil / water interface, which is much higher than the alkyl chain density in the monolayer formed by conventional single-tail single-head surfactants, thereby significantly increasing the interaction between the monolayer and crude oil, making it easy to obtain ultra-low interfacial tension, reaching 10 -3 ~10 -4 mN / m order of magnitude.
[0072] Example 6 Compounding to reduce interfacial tension
[0073] The above APES was dissolved in Daqing simulated formation water, and the interfacial tension of crude oil in three types of Daqing oil layers was measured by the rotating drop method at 45°C. The interfacial tension could only reach 10 -1 ~10 -2 This is because the oil in the third type of Daqing reservoir is heavier, and its equivalent carbon atom number is greater than C 10 In this case, adding a small amount of more lipophilic surfactant to the APES solution can obtain ultra-low interfacial tension. 10 Alkyl Glyceryl Ether Hydroxypropyl Sulfobetaine (diC 10 GE-HSB) was used as a lipophilic surfactant and was compounded with APES to form APES / diC 10 The mass ratio of GE-HSB is 85 / 15. It can be seen that ultra-low interfacial tension can be obtained in the range of total concentration of 0.03-1.25wt.%, and the interfacial tension reaches 10 -4 mN / m order of magnitude, the specific value is 0.00041~0.00091mN / m, such as Fig. 9 Compared with the APES system for Daqing light oil, the total surfactant concentration range of this binary system is one order of magnitude lower and more economically effective, while the mass fraction of APES reaches 85%, which is still the main surfactant.
[0074] These examples show that the nonionic-anionic composite surfactant derived from the nonionic intermediate of the present invention has excellent oil displacement performance and can meet the needs of alkali-free oil displacement.
[0075] Comparative Example 1
[0076] Preparation of block compounds without mixed structure: C 16 The method comprises the following steps: firstly adding propylene oxide (PO) to gubetal alcohol in the presence of 100 ppm DMC catalyst, wherein 30 mol PO is added to each mol gubetal alcohol, the reaction temperature is 140° C., and the reaction is carried out in a non-stirring circulating spray reactor; after the reaction is completed, the product is transferred to another reactor, and an alkali catalyst (KOH) is added at a concentration of 0.3%, and 15 mol EO is added to each mol gubetal alcohol. EO is added for ethoxylation reaction, and the reaction temperature is controlled at 150° C. until the reaction is completed, and the reaction is appropriately cooled, and the catalyst is neutralized with glacial acetic acid to obtain a block compound C. 16 Cufibrate alcohol-(PO) 30 (EO) 15 H. The two-step reaction took a total of 8 h.
[0077] The viscosity results of the obtained block compounds are shown in Table 1.
[0078] Table 1 Polyether compounds with different structures (C 16 Viscosity of alcohol (30 mol PO + 15 mol EO) and its comparison with the viscosity of AEO3
[0079]
[0080]
[0081] Compared with compounds containing block structures, the compounds containing mixed polymer structures of the present invention have the following advantages in production and subsequent applications:
[0082] (1) In terms of production, the use of mixed polymerization can simplify the reaction steps and shorten the reaction time, thereby reducing the production cost. For example, when a block structure is used, it takes about 8 hours to add 30 mol PO and 15 mol EO, and different catalysts need to be used for the addition of PO and EO, and the reactor needs to be replaced in the middle; while the reaction takes only 2 hours when the structure of the present invention is used, and there is no need to replace the catalyst and reactor.
[0083] (2) Due to the large number of moles of added PO and EO, the product obtained by using the block structure is usually in a paste state with poor fluidity and is not convenient for pipeline transportation, which will bring inconvenience to packaging and subsequent production and feeding. However, by using the structure of the present invention, the obtained product is a transparent liquid at room temperature with good fluidity and is easy to pump. Fig.10 shown.
[0084] (3) For the subsequent sulfation operation, the most advanced process is the gas SO3 falling film sulfation process. For example, the widely used anionic-nonionic composite surfactant fatty alcohol polyoxyethylene ether sulfate (AES) is produced by using short-chain fatty alcohol polyoxyethylene ether AEO3 through the gas SO3 falling film sulfation process. This process is continuously operated, has high production efficiency, low cost, no three wastes, and stable product quality, but requires the raw materials to have good fluidity and be easy to form a film at the reaction temperature. Obviously, the product obtained by using the block structure is a paste with a viscosity of >10,000mPa·s at room temperature. The gas SO3 falling film sulfation process cannot be used. Generally, only aminosulfonic acid can be used as the sulfonating agent and sulfation is carried out through intermittent reaction. In order to ensure the stability of the product, the obtained ammonium salt still needs to be replaced with sodium salt, and this process will release ammonia (NH3). In order to prevent environmental pollution, ammonia needs to be absorbed, which complicates the production process. By adopting the mixed polymer structure of the present invention, the intermediate has excellent fluidity and a viscosity close to that of AEO3, as shown in Table 1, so the gas SO3 falling film sulfonation process can be directly adopted for sulfation.
Claims
1. A type of oil displacing agent, characterized in that: The structure is RA-R'; Among them, A is a structure formed by the polymerization of PO and EO. U1 and U2 are different and can be independently selected from: x is the number of moles of PO, selected from an integer between 15 and 30; y is the number of moles of EO, selected from an integer between 10 and 20; and A is not the following block structure R' is -SO3Na; R is derived from C16 gubertol and has the following structure containing two long-chain alkyl groups: R1 and R2 are both hexyl.
2. A method for preparing the oil displacing agent according to claim 1, characterized in that: The process includes the following: (1) Propylene oxide and ethylene oxide are premixed, and then mixed with C16 gubertol and a catalyst, and a mixed polymerization reaction is carried out in one pot under an inert atmosphere. After the reaction is completed, a compound intermediate R (PO+EO) having a mixed polymerization structure of propylene oxide (PO) and ethylene oxide (EO) is obtained. x+y H; (2) Use sulfating agent to treat intermediate R(PO+EO) x+y H is sulfated to obtain a nonionic-anionic composite surfactant R (PO+EO) x+y -SO3Na.
3. The method according to claim 2, characterized in that Sulfating agents include gaseous SO3, chlorosulfonic acid or aminosulfonic acid.
4. The method according to claim 2, characterized in that: The sulfation process includes: using gaseous SO3 as a sulfating agent, and reacting the intermediate R (PO + EO) through a falling film reactor. x+y H for sulfation.
5. The method according to claim 2, characterized in that: A SO3 / air mixture is used as the sulfating agent, and the SO3 concentration is ≤5%.
6. The method according to claim 4, characterized in that Intermediate R(PO+EO) x+y The molar ratio of H to SO3 is 1:1.
05.
7. The method according to any one of claims 3 to 6, characterized in that: The reaction temperature is 55-60°C. After the reaction is completed, the solution is neutralized with NaOH aqueous solution to pH 8-9.
8. Use of the oil displacement agent according to claim 1 in the field of oil production.
Citation Information
Patent Citations
Low-tension foaming agent composition and preparation method thereof
CN103740357A
Double-long-chain anionic-nonionic composite surfactant for oil displacement and preparation method thereof
CN111073621A
Surface active agent, and its preparing method and use
CN1470317A